2013
DOI: 10.1016/j.surfcoat.2013.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu on the microstructural and mechanical properties of sputter deposited Ni-Ti thin films

Abstract: The microstructure of sputter deposited Ti-rich Ni-Ti thin films doped with Cu in the range 0-20.4 at.% and annealed for 1 h at 500 and 600°C has been investigated and correlated with the mechanical properties of the films measured by depth-sensing nanoindentation. X-ray diffraction analysis showed the microstructural evolution of Ni-Ti thin films when doped with Cu and annealed at different temperatures. Heat treatments promoted the nucleation and growth of Ti 2 Ni precipitates in Ti-rich Ni-Ti thin films, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…Increasing the power to 2.2 kW increased the amount of copper mixed into the fusion zone (figure 4) and grew the equiaxed dendritic microstructure shown in figure 2(b), which is similar to previous work by Callisti et al [26]. The greater dissolution and mixing of the copper base metal into the fusion zone was due in part to the copper liquid absorbing more laser energy than copper solid [23].…”
Section: Microstructure Composition and Micro-hardnesssupporting
confidence: 86%
“…Increasing the power to 2.2 kW increased the amount of copper mixed into the fusion zone (figure 4) and grew the equiaxed dendritic microstructure shown in figure 2(b), which is similar to previous work by Callisti et al [26]. The greater dissolution and mixing of the copper base metal into the fusion zone was due in part to the copper liquid absorbing more laser energy than copper solid [23].…”
Section: Microstructure Composition and Micro-hardnesssupporting
confidence: 86%
“…Mechanical characterisation revealed that the elastic modulus of the thin film gradually reduced in proportion to increasing number of Ag solute atoms in the Ti 3 Au matrix [ 44 46 ] from 136 to 82 GPa, and variation in results increased due to increasing Ag agglomeration on the surface. Ti 3 Au samples doped with Cu report elastic modulus values very close to that of the standard Ti 3 Au thin films and with more consistent values in the range 134 to 146 GPa and could be related to the higher reported Young’s modulus of Cu (128 GPa) compared to Ti (112 GPa) and Ag (73 GPa) [ 44 , 60 ], grain refinement and constraining of neighbouring grains [ 62 ], and the precipitation of the Ti-Cu intermetallic leading to stiffening of the Ti 3 Au thin film matrix with increasing Cu concentration [ 44 , 46 , 61 ]. While one current limitation with these alloys is that their elastic modulus values are still higher than that of natural bone (30 GPa) [ 87 ], the observed reduction in the elastic modulus of the standard Ti 3 Au intermetallic when alloyed with yielding elements like Ag could be further explored to enable load bearing implants to efficiently transfer loads to developing bones and reduce the stress shielding effect [ 88 ].…”
Section: Discussionmentioning
confidence: 90%
“…Further, the precipitation of Ti-Cu intermetallic compounds at the lower Cu concentration of 7 at%, leads to stiffening of the Ti 3 Au thin film matrix with increasing Cu concentration [ 44 , 46 , 61 ]. The observed stabilization of elastic modulus values for Cu dopant concentrations above 2.8 at% can also be explained due to grain refinement and the constraining effect of neighbouring grains [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar tendency in the microhardness with the addition of Cu was reported earlier. 33 The alloy with the lowest microhardness value (TNC2) was projected to be more ductile than the other alloys.…”
Section: Microscopic Studiesmentioning
confidence: 99%